The Chaperone-Like Activity of α-Synuclein Attenuates Aggregation of Its Alternatively Spliced Isoform, 112-Synuclein In Vitro: Plausible Cross-Talk between Isoforms in Protein Aggregation - Manda, Krishna Madhuri; Yedlapudi, Deepthi; Korukonda, Srikanth; Bojja, Sreedhar; Kalivendi, Shasi V. (PloS one, 2014)
Abnormal oligomerization and aggregation of α-synuclein (α-syn/WT-syn) has been shown to be a precipitating factor in the pathophysiology of Parkinson's disease (PD). Earlier observations on the induced-alternative splicing of α-syn by Parkinsonism mimetics as well as identification of region specific abnormalities in the transcript levels of 112-synuclein (112-syn) in diseased subjects underscores the role of 112-syn in the pathophysiology of PD. In the present study, we sought to identify the aggregation potential of 112-syn in the presence or absence of WT-syn to predict its plausible role in protein aggregation events. Results demonstrate that unlike WT-syn, lack of 28 aa in the C-terminus results in the loss of chaperone-like activity with a concomitant gain in vulnerability to heat-induced aggregation and time-dependent fibrillation. The effects were dose and time-dependent and a significant aggregation of 112-syn was evident at as low as 45 °C following 10 min of incubation. The heat-induced aggregates were found to be ill-defined structures and weakly positive towards Thioflavin-T (ThT) staining as compared to clearly distinguishable ThT positive extended fibrils resulting upon 24 h of incubation at 37 °C. Further, the chaperone-like activity of WT-syn significantly attenuated heat-induced aggregation of 112-syn in a dose and time-dependent manner. On contrary, WT-syn synergistically enhanced fibrillation of 112-syn. Overall, the present findings highlight a plausible cross-talk between isoforms of α-syn and the relative abundance of these isoforms may dictate the nature and fate of protein aggregates.